High-frequency groceries prices: Evidence from Czechia - Anna Pavlovova (Charles University in Prague, Institute of Economic Studies (IES), 2023)
How often do online retailers change prices? Are there any differences in their price rigity? I collected and analysed more than 4 million daily prices of online grocery retailers from Czechia during the unprecedented period between January 2020 and April 2021. There are substantial differences in pricing among the four retailers. The mean number of all price changes ranges among the retailers between 3.10 and almost 11 per year. Most of the price changes are temporary. Retailers change prices permanently on average between 0.68 to 4.04 times per year. The differences in pricing persist even after the disaggregation of the products into individual categories and even in the estimation of the within-between model of the probability of price change. An in-depth analysis of temporary price adjustments is crucial to robustly assess pricing and price rigidity. It is likely to explain part of the discrepancy in pricing found across the retailers.
Keywords: E30; D22; L11; L81; M21; 330; price setting; price exibility; scraped prices; temporary price changes